THE EFFECT OF USING ROLE PLAYS TECHNIQUE AMONG ACCOUNTING STUDENTSâ SPEAKING ACHIEVEMENT AT STIE MUHAMMADIYAH BERAU - Milarisa, Surti (English Education Study Program Universitas Muhammadiyah Palembang, 2018)
The objective of this research is to find out the effect of role play performance on accounting studentsâ speaking achievement at STIE Muhammadiyah Berau.This research is an experimental research which were consist of 20 collegians as sample. They were taught by using role play technique. The test given was in form of oral performance test. The samples were given pretest before treatment and posttest after treatment. The criteria of scoring were fluency, content and pronunciation. To know the effect of the role plays technique on the collegiansâ speaking achievement, t-test was used. The result shows that teaching speaking using role play technique gave positive effect to the studentsâ speaking ability.